Role of dietary energy and protein proportions on serum inflammatory factors, antioxidant capacity, and rumen microbiota in postpartum weaned female yak - Yanbin Zhu; Yangji Cidan; Sijia Lu; Zhuoma Cisang; Deji Gusang; Quzha Danzeng; Munwar Ali; Muhammad Usman Saleem; Kun Li; Wangdui Basang (BMC Microbiology)
Abstract Background The economically important yaks have a low reproductive rate of only one calf every two years or two calves every three years, which significantly limits the development of the yak industry. Protein and dietary energy are important factors affecting the productive performance of ruminants. Methods This study examined the effects of three different feed formulas (FA: high-energy and high protein, FB: high-energy and low protein, and FC: low-energy and high protein) on the health status of postpartum weaned female yaks. Results Results indicated that significantly lower inflammatory factors of IL-1β and IL-6, and higher antioxidant capacity enzymes of T-AOC and GSH-Px, and lower MDA levels were examined in FA and FB. Analysis of the rumen microbiota in all groups showed that the experimental group, especially the FA group, had an alpha diversity. Firmicutes increased while Bacteroidota decreased in group FA and FB, resulting in a higher Firmicutes to Bacteroidota ratio. Additionally, the abundance of Proteobacteria, Spirochaetota, and Elusimicrobiota was significantly decreased in the groups with different diets in FA and FB. At the genus level, the abundance of Prevotella, Ruminococcus, UCG-002, and Treponema was significantly lower in the two groups, FA and FB, while the abundance of Butyrivibrio, Christensenellaceae_R-7_group, UCG-005, and Family_XIII_UCG-001 was higher in the two groups. The Lachnospiraceae_AC2044_group was more abundant in the two groups of FB and FC. Also, Saccharomonas was significantly more prevalent across all the experimental groups. Based on these results, a high-energy diet appears to benefit the health and recovery of postpartum yaks, although further adjustments to the dietary protein ratio may be beneficial. Conclusion Our study provides recommendations for improving the physical health of postpartum weaned female yaks, reducing the time from calving to estrus, and enhancing the reproductive capacity of yaks in Tibetan areas.